2016
DOI: 10.15698/mic2016.03.484
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated cytoplasmic granule formation in quiescent and non-quiescent cells upon chronological aging

Abstract: Stationary phase cultures represent a complicated cell population comprising at least two different cell types, quiescent (Q) and non-quiescent (NQ) cells. Q and NQ cells have different lifespans and cell physiologies. However, less is known about the organization of cytosolic protein structures in these two cell types. In this study, we examined Q and NQ cells for the formation of several stationary phase-prevalent granule structures including actin bodies, proteasome storage granules, stress granules, P-bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…Lee et al . also proved that the Q cells reenter the mitotic cycle more quickly after nutrition replenishment 5, which further establishes the phenotypical difference between the two cell types (Fig. 1).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Lee et al . also proved that the Q cells reenter the mitotic cycle more quickly after nutrition replenishment 5, which further establishes the phenotypical difference between the two cell types (Fig. 1).…”
supporting
confidence: 64%
“…In this issue, Lee et al . reports that distinct granules are formed in Q and NQ cells, which determines their respective cell fates 5. The authors asked whether different kinds of granules were distributed uniformly between Q and NQ cells, and found that most granule structures are enriched in NQ cells with the exception of Hsp42-associated stationary phase granules (Hsp42-SPGs) (Fig.…”
mentioning
confidence: 99%
“…The other part was placed in fresh YPD media for 2.5 h and then subjected to the same heat treatment. Cell survival rates were measured as colony-forming units after 3 days of incubation at 28 C.As a rebudding assay, more than 100 unsorted stationary-phase cells were placed on agarose pads and monitored by time-lapse microscopy at 15 min intervals for at least 12 h[82]. Only unbudded cells at the beginning of the recording period were monitored.…”
mentioning
confidence: 99%
“…Unlike dividing cells, Q cells are thermotolerant (5) and possess cell walls resistant to zymolyase (6). NQ cells, on the contrary, are less resistant to these treatments and are prone to genomic instability (5,7,8).…”
mentioning
confidence: 99%
“…Unlike dividing cells, Q cells are thermotolerant (5) and possess cell walls resistant to zymolyase (6). NQ cells, on the contrary, are less resistant to these treatments and are prone to genomic instability (5,7,8). Because of their short life cycle and the extensive availability of molecular tools, budding yeast are an excellent model in which to study the unique biology of quiescence (9).…”
mentioning
confidence: 99%